Range of the tolerance in the solution of integrals for the Moment Method (MM) during the computes of thin antennas of straight wires (2015)
Taking advantage of the excellent opportunities offered by the professional MATLAB software; an analysis of the solution of integrals generated by the Method of Momentsin conjunction with the method of the Adapted Points and their influence on the final outcome of the simulation of thin antennas of straight and electrically short conductives is made. It was taken into consideration the recommendation to use a basisfunction or polynomial ofsimple expansion and organized in power series of few terms in the case of thin symmetrical dipoles and electrically short antennas, and also some recommendations are made.